Retrospective Analysis of Cases with Guillain-Barré Syndrome in Pediatric Intensive Care Unit - Hasan Serdar Kıhtır; Nermin Ankay; Esra Şevketoğlu; Mey Talip Petmezci; Osman Yeşilbaş; Zeynep Kıhtır (Galenos Yayinevi, 2017)
Introduction: The aim of this study was to evaluate treatment approaches towards Guillain-Barré syndrome and treatment response in patients with Guillain-Barré syndrome admitted to the pediatric intensive care unit. Methods: We retrospectively evaluated patients aged between 1 month and 18 years who were admitted to our pediatric intensive care unit between January 2006 and January 2016 with the diagnosis of Guillain-Barré syndrome. Results: A total of 27 patients (10 girls; 37%) were included in this study. The mean age of the patients was 6.24 years (IQR: 4.07-10.03). Nine patients (33.3%) had a Hughes functional grading scale score of 3, 16 (59.3%) had 3 and 2 (7.4%) had 5. Electrophysiological studies were performed in 22 cases (81.4%) and acute inflammatory demyelinating polyneuropathy was detected in 10 cases (45.5%), acute motor axonal neuropathy in 9 cases (40.9%), and acute motor and sensory axonal neuropathy in 1 case (4.5%). Two (9.1%) patients were evaluated as normal. All the patients were administered intravenous immunoglobulin (IVIG). In 12 (52.17%) patients, plasmapheresis was performed for a median of 8 sessions (5-9) before IVIG. Mechanical ventilation was required in 6 patients (22.2%) and was performed for a median of 24 days (5-41). The mean period of time of the first supported sitting was 6 (3-10) days and the mean period of time of the first walking with aid was 9 (7-15) days. Conclusion: Although there have been studies claiming that plasmapheresis was more successful, it has been generally accepted that plasmapheresis and IVIG have the same efficacy. Under the conditions of our country, we believe that both plasmapheresis and IVIG can be safely used at experienced units in patients with Guillain-Barré syndrome who need intensive care treatment.